Taking messages from the day forward to Rio+20 and beyond - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Live from Agriculture and Rural Development Day at Rio+20, 18 June 2012 http://www.agricultureday.org Synthesis of messages: Ann Tutwiler, Deputy Director General, Food andAgriculture Organization of the United Nations (FAO) Panel response: Carl Hausmann, Vice Chair, CGIAR Consortium Board; Pedro Antonio Arraes Pereira, President of the Brazilian Agricultural Research Corporation (Embrapa) Join the discussion: #rio4ag http://www.twitter.com/agricultureday http://www.facebook.com/agricultureday